Fourier Transform Spectroscopy with Partially Scanned Interferograms as a Tool to Retrieve Atmospheric Gases Concentrations from High Spectral Resolution Satellite Observations - Methodological Aspects and Application to IASI - Serio, Carmine; Masiello, Guido; Grieco, Giuseppe (IntechOpen, 2012)
None